2009
DOI: 10.3758/brm.41.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Systematic behavior research for understanding consumer decision making

Abstract: Business survival in dynamic and competitive environments depends on an ability to analyze consumption information and determine which products consumers want. Collecting consumption data, hence, becomes a primary activity for product and marketing strategy development. Businesses typically gather consumption data from consumers shopping in the retail market. Data for items purchased are transmitted through retail information systems to inventory controllers for product-ordering decisions. Although such decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…After obtaining the accumulated A‐C‐V linkage frequencies for each sample country, the authors put them into the summary implication matrix for constructing the cognitive structure map of each country. The cognitive A‐C‐V structures of credit card web pages were constructed using the cutoff value originally developed by Pieters et al (1995) because their criteria can predetermine the cutoff value objectively (Lin, 2009). The main principle of determining the cutoff value is to use fewer A‐C‐V linkages to present the most content of cognitive structures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After obtaining the accumulated A‐C‐V linkage frequencies for each sample country, the authors put them into the summary implication matrix for constructing the cognitive structure map of each country. The cognitive A‐C‐V structures of credit card web pages were constructed using the cutoff value originally developed by Pieters et al (1995) because their criteria can predetermine the cutoff value objectively (Lin, 2009). The main principle of determining the cutoff value is to use fewer A‐C‐V linkages to present the most content of cognitive structures.…”
Section: Methodsmentioning
confidence: 99%
“…The MEC model links a product's attributes to the consequences for consumers of using the product or service, and to the personal values that consumers place on its use. The linkage hierarchies of attribute‐consequence‐value allow marketers to understand consumers' cognitive structures clearly, enabling them to develop and assess effective advertising strategies (Lin, 2009; Lin and Wang, 2008; Parry, 2002; Reynolds and Olson, 2001; Wagner, 2007). Reynolds and Gutman (1988) concluded that the series of cognitive hierarchies in the MEC model can be applied to formulate advertising strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many articles have focused on the integration of multivariable and MEC analyses (Fu & Wu, 2010;Goldenberg et al, 2000;Langerak et al, 1998;Lin, 2009;Orsingher & Marzocchi, 2003), while only some have mentioned the weaknesses of using the MEC methodology (Kaciak & Cullen, 2006;. The major issues related to the MEC methodology are as follows:…”
Section: Issues and Weaknesses Of Mec Ladderingmentioning
confidence: 99%
“…Desirable or undesirable consequences are post-consumption ones, which can be positive or negative. Positive feelings denote the benefits perceived by consumers, while negative feelings represent associated or perceived risks that influence consumer willingness to repurchase a product (Goldenberg, Klenosky, O’Leary, & Templin, 2000; Lin, 2009). Consequently, several researchers have adopted benefits (positive feelings) instead of consequences (Lin, 2003; Vriens & Ter Hofstede, 2000; Woodside, 2004), thus replacing the original attribute-consequence-value ( A - C - V ) chains in MEC analysis with attribute-benefit-value ( A - B - V ) chains.…”
Section: Literature Reviewmentioning
confidence: 99%